Sustainable agricultural intensification in forest frontier areas - Maertens, Miet; Zeller, Manfred; Birner, Regina (Wiley, 2006)
The Lore Lindu region in Indonesia—as in many forest frontier areas in Southeast Asia—has experienced rapid deforestation due to agricultural expansion in the uplands, at the forest margins. This has resulted in aggravated problems of erosion and water availability, threatening agricultural productivity growth. At the same time, technical progress is promoting agricultural intensification in the lowlands. In this article, we examine how improved technologies for paddy rice cultivation in the lowlands have affected agricultural expansion and deforestation in the uplands. The question of a "forest-saving" or "forest-clearing" effect related to technical innovation is important from a sustainable development perspective and remains a controversial issue in the literature. We address this question for the Lore Lindu region with an empirical model in which expansion in the lowlands and the uplands is estimated simultaneously. We use data from an extensive village survey conducted in the region, combined with GIS data. To guide the empirical analysis, we develop a theoretical framework based on a Chayanov-type agricultural household model. The model analyzes farmers' land allocation decisions, taking into account the lowland–upland dichotomy in the agricultural sector. The empirical findings, corroborated by the analytically derived results, show how technical progress for lowland production affects land use at the forest margins and how these effects depend on the factor-intensity of the technology. The findings imply specific rural development policies for sustainable agricultural intensification in forest frontier areas.